Effect of suction on local scour downstream of a rigid structure - Chew, Jing Xuan (2016)
The influence of suction at the downstream of a fixed apron was investigated in a laboratory flume. Experiments were conducted at a fixed water depth with varying flow rate and suction rate at fixed suction position. The results clearly show that suction has an adverse effect in increasing the depth of scour hole downstream of the apron in all the experiments. The adverse effect is obvious even with low channel flow. However, there exist instability in low channel flow runs, where the dimensionless graphical data reveals that they do not fit in the trend of runs with higher flow rate. For other runs with varying suction rate, the 2-D scour profile generally follows the suction rate; higher suction results in deeper scour depth. However, at low suction rate, the scour depth does not coincide with the magnitude of suction rate. There is significant distinct difference for very low suction rate runs of as low as 0.029% of channel flow rate, as compared to non-suction runs. In another words, it tells us that only a minute suction is required to generate produce the suction effect on the sediment.